Comparison of Lipid Peroxidation and Several Antioxidants in Blood of Normally Calved and Dystocia Affected Cows and Their Newborn Calves - Kandemir, F. M.; Erisir, M.; Yuksel, M. (Israel Veterinary Medical Assoc, 2016)
The changes of malondialdehyde (MDA) concentrations in plasma and of enzymatic antioxidants like glutathione peroxidase (GSHPx), catalase (CAT) activities, non-enzymatic antioxidants like glutathione (GSH) concentrations in blood of normally calved and dystocia affected cows and their newborn calves were investigated. The study included 8 normally calved cows, 8 dystocic cows and their neonates. Calves of dystocic cows were delivered by traction from the birth canal. The MDA, GSH concentrations (P<0.001) and CAT activity (P<0.01) were significantly higher in dystocia affected cows compared to the normally calved cows. MDA concentrations were significantly higher in the calves of dystocia affected cows compared to the calves of normally calved cows (P<0.001), but CAT activity and GSH concentration were significantly lower (P<0.01). There were no significant differences in the GSHPx activity between the groups. In both dystocia affected cows' and normally calved cows' calves, the plasma MDA concentrations were higher than in their mothers. Moreover the CAT and GSHPx activities and GSH concentration in the normally calved cows' calves were higher than in their mothers'. Our results suggest that lipid peroxidation and antioxidant status change during dystocia, and these changes may affect the fetus by creating oxidative stress.
Keywords: Dystocia; Cows; Calves; Lipid peroxidation; Antioxidants